2009
DOI: 10.1029/2008jb006192
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of the westernmost Ryukyu subduction zone and the serpentinization of the fore‐arc mantle

Abstract: [1] Three-dimensional tomographic images of the subducting Philippine Sea slab and the fore-arc mantle beneath NE Taiwan and the westernmost Ryukyu were generated in this study. More than 5600 events recorded simultaneously by seismic networks in Taiwan and Japan were relocated for the inversion for variations in V P , V S , and V P /V S . Analysis of the trade-off between the data variance reduction and model variance helps to determine the appropriate strictness for regularization to avoid either overinterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 44 publications
(86 reference statements)
6
48
0
Order By: Relevance
“…Moreover, the thickness of the serpentinized layer estimated by McCormack et al (2013) is only 6 km, which is smaller than the node intervals (horizontal 10 km; vertical 7.5 km) used in this study; thus, the resolution is too low to distinguish a 6-kmthick layer within the surrounding mantle. Chou et al (2009) investigated the velocity structure of the mantle wedge above the subducted PHS in the TaiwanRyukyu junction zone (121.8°E) and showed that approximately 60% serpentinized mantle wedge lies on the PHS at a depth of 50 km. Thus, a serpentinized area is distributed in the mantle wedge beneath the southern Ryukyu arc.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the thickness of the serpentinized layer estimated by McCormack et al (2013) is only 6 km, which is smaller than the node intervals (horizontal 10 km; vertical 7.5 km) used in this study; thus, the resolution is too low to distinguish a 6-kmthick layer within the surrounding mantle. Chou et al (2009) investigated the velocity structure of the mantle wedge above the subducted PHS in the TaiwanRyukyu junction zone (121.8°E) and showed that approximately 60% serpentinized mantle wedge lies on the PHS at a depth of 50 km. Thus, a serpentinized area is distributed in the mantle wedge beneath the southern Ryukyu arc.…”
Section: Resultsmentioning
confidence: 99%
“…If the same inversion technique and model parameterization is used to invert for V P and V S , the resulting models can be compared quantitatively as in e.g. Chou et al (2009) and Hung et al (2011).…”
Section: Measuring Residualsmentioning
confidence: 99%
“…[40] Theoretically, dln(V P /V S ) is simply the difference between dlnV P and dlnV S [e.g., Chou et al, 2009]. Although Figure 6.…”
Section: Comparison Among Regularization Schemesmentioning
confidence: 99%
“…[9] It is important to point out that although theoretically the relationship among dlnV P , dlnV S , and dln(V P /V S ) is simple [e.g., Chou et al, 2009], reliable estimates of dln(V P /V S ) requires a careful selection of data to ensure that only sourcereceiver pairs common to both P and S wave are being used. Subsequently, the entire process of inversion, along with additional resolution tests, is carried out anew.…”
Section: Introductionmentioning
confidence: 99%